Relationship between roadside features and road traffic accidents along KM 3 - KM 27 of Jalan Kuantan-Gambang - Marzida, Abdul Manaf (2010)
Road traffic accident cases are increasing year by year. There are many factors which can lead to road traffic accidents such as vehicle speed, weather conditions, poor road conditions, and poor vehicle conditions. There are many studies that have been carried out to study the causes and effects of the road traffic accidents. However, only limited research has been done on the relationship between the roadside development and the number of traffic accident cases happened. Hence, this research on the relationship between the roadside features and the road traffic accidents along KM 3 until KM 27 of Jalan Kuantan - Gambang has been carried out. This research has been done in order to identify the existing critical distance of roadside features along KM 3 until KM 27 of Jalan Kuantan - Gambang and to study the relationship between the roadside features and the number of traffic accident cases. This research has been done by gathering the traffic accident data from the Polis Diraja Malaysia (PDRM). Then the data was tabulated and gathered as well as arranged into order by using Microsoft Excel. Next, the tabulated data was inserted into SPSS software in order to analyse them. The data was analysed - by using the descriptive analysis and the bivariate correlation. The step has been done to get the relationship between the dependent variables and the independent variables. The dependent variables are the roadside features and the independent variables are the number of traffic accident cases happened along Jalan Kuantan - Gambang. This research has proven that there is a strong relationship between the critical distance of the roadside features with the increasing number of road traffic accidents. This research could produce a better findings if there are many other aspects that could be measure such as the road surface conditions and the types of road which is rural or urban.